The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0190850
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of peptide phage display to investigate hotspots on IL-17A and what it means for drug discovery

Abstract: To date, IL-17A antibodies remain the only therapeutic approach to correct the abnormal activation of the IL-17A/IL-17R signaling complex. Why is it that despite the remarkable success of IL-17 antibodies, there is no small molecule antagonist of IL-17A in the clinic? Here we offer a unique approach to address this question. In order to understand the interaction of IL-17A with its receptor, we combined peptide discovery using phage display with HDX, crystallography, and functional assays to map and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 27 publications
(53 reference statements)
2
22
0
1
Order By: Relevance
“…A single- to double-digit micromolar starting affinity, as reported here, is often observed for peptide identification from phage display. For example, peptides isolated to Japanese encephalitis virus, insulin-degrading enzyme, or IL17A had affinities in the 2.5–12 μ m range (4244). Subsequent affinity maturation has been successfully employed to achieve affinities in the nanomolar range (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single- to double-digit micromolar starting affinity, as reported here, is often observed for peptide identification from phage display. For example, peptides isolated to Japanese encephalitis virus, insulin-degrading enzyme, or IL17A had affinities in the 2.5–12 μ m range (4244). Subsequent affinity maturation has been successfully employed to achieve affinities in the nanomolar range (42).…”
Section: Discussionmentioning
confidence: 99%
“…For example, peptides isolated to Japanese encephalitis virus, insulin-degrading enzyme, or IL17A had affinities in the 2.5–12 μ m range (4244). Subsequent affinity maturation has been successfully employed to achieve affinities in the nanomolar range (42). Additional peptide phage libraries can also be constructed by randomizing the residues that are adjacent to the ones critical for the interaction (soft randomization) based on structural information and thus improve the affinity of the parental FYLIR peptide.…”
Section: Discussionmentioning
confidence: 99%
“…IL-23 bound phage was eluted by 100 mM of triethylamine and was immediately neutralized by 1 M Tris/HCl pH 6.8. After three rounds of selection, phage was screened against IL-23, IL-12, and background neutravidin-coated plates as described previously using filter-lift and phage-ELISAs [15].…”
Section: Phage Display Library Construction Selection and Screeningmentioning
confidence: 99%
“…As a result, a gradual enrichment of p19 binders was observed in the selected pool as the selection progressed. After three rounds of selection, phage pool was deconvoluted by filter-lift and single point ELISA [15]. Sequence analysis of specific p19 binders indicated that more than 40% of clones share a common motif comprised of phenylalanine-Glycine-Leucine/Threonine (FGL/T).…”
Section: Selection Of Phage Libraries Against Il-23mentioning
confidence: 99%
“…At the protein–protein interface, α-helices tend to bind into the groove of their binding partner, and as a result, helix mimetics have been of great interest. A number of methods exist which aid in the discovery of new PPIs and facilitate the discovery of molecules to bind PPIs, including high throughput screening [ 20 ], phage display [ 21 ], crosslinking [ 22 ], computational studies [ 23 ] and structural based design, to name a few.…”
Section: General Structure Of Ppismentioning
confidence: 99%